COMPLICATIONS ASSOCIATED WITH INTERNAL ILIAC LIGATION IN THE CONTEXT OF SEVERE POST-PERIPARTUM HYSTERECTOMY BLEEDING - ULLAH , S; QAZI , Q; KHAN , N; KHAN , H; SHAHBAZ , N (Biological and Clinical Sciences Research Journal, 2024)
Severe post-peripartum hysterectomy bleeding poses a critical threat to maternal health, necessitating swift and effective interventions to ensure favorable outcomes. The main objective of the study is to find the potential complications associated with internal iliac ligation in the context of severe post-peripartum hysterectomy bleeding. This prospective observational study was conducted in the gynecology and obstetrics department of Lady Reading Hospital Peshawar from June 2022 til the required sample size is obtained. The study included women who had significant and profuse post-peripartum hysterectomy bleeding. All women with post-peripartum hysterectomy hemorrhage were identified, focusing specifically on cases where internal iliac ligation was employed as an intervention. The demographic information, including patient age, parity, medical history, and obstetric details, was collected on predesigned proforma. Data was collected from 196 patients. The mean age of the patients was 31.5±4.2 years. About 97% of patients were multiparas, and all patients presented with postpartum hemorrhage (100%). The mode of delivery was vaginal in 89% of cases. It is concluded that internal iliac ligation, while effective in controlling severe post-peripartum hysterectomy hemorrhage, presents a nuanced landscape marked by a low incidence of vascular (1.5%) and ureteric (0.5%) injuries. Consequently, we believe that procedure is worth try in the face of catastrophic uncontrolled haemorrhage, especially in low-income countries.